2010
DOI: 10.1002/j.2161-1882.2010.tb00045.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Sibling Maltreatment and College Students' Sense of Well‐Being

Abstract: Empirical research on sibling abuse has been overwhelmingly absent from the professional literature. This exploratory study used a survey instrument to investigate the question of whether the experience of sibling abuse influences the sense of well-being in college students. A linear multiple regression analysis indicated that experience with sibling abuse, either as a survivor or as a perpetrator, does have an impact on perception of well-being. Implications of these findings for future research are discussed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…Failing to label such behaviors as abuse has contributed to the minimization of sibling violence (Hardy 2001;Hardy et al 2010). Additionally, as other literature has documented, when families do not properly address sibling abuse, it may be allowed to continue for years (Bass et al 2006;Carlson et al 2006;Morrill-Richards and Leierer 2010;Rudd and Herzberger 1999). Our participants largely felt left to fend for themselves against a violent sibling.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Failing to label such behaviors as abuse has contributed to the minimization of sibling violence (Hardy 2001;Hardy et al 2010). Additionally, as other literature has documented, when families do not properly address sibling abuse, it may be allowed to continue for years (Bass et al 2006;Carlson et al 2006;Morrill-Richards and Leierer 2010;Rudd and Herzberger 1999). Our participants largely felt left to fend for themselves against a violent sibling.…”
Section: Discussionmentioning
confidence: 80%
“…Our participants largely felt left to fend for themselves against a violent sibling. This meant that the abuse lasted for an average of 13 years, and such longterm abuse has been associated with serious mental health consequences (Button and Gealt 2010;Eriksen and Jensen 2006;Morrill-Richards and Leierer 2010;Noland et al 2004;Rudd and Herzberger 1999). Furthermore, it has been shown that sibling abuse victims are traumatized when others, particularly parents, are ineffective in protecting them, especially when they do not take the abuse seriously (Bass et al 2006;McVeigh 2003;Tucker and Kazura 2013).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations